2006
DOI: 10.15288/jsa.2006.67.86
|View full text |Cite
|
Sign up to set email alerts
|

A developmental study of heavy episodic drinking among college students: the role of psychosocial and behavioral protective and risk factors.

Abstract: ABSTRACT. Objective: A theory-based protection/risk model was applied to explain variation in college students' heavy episodic drinking. Key aims were (1) to establish that psychosocial and behavioral protective factors and risk factors can account for cross-sectional and developmental variation in heavy episodic drinking, and (2) to examine whether protection moderates the impact of risk on heavy episbdic drinking. Method: Random-and fixed-effects maximum likelihood regression analyses were used to examine da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 61 publications
2
57
0
3
Order By: Relevance
“…our findings provide tangible evidence that this important context remains a salient one for alcohol use into the college years. second, although we did not directly investigate the importance of risk and protective factors, our findings can also be interpreted within this framework (hawkins et al, 1992;Jessor et al, 1995;Jessor et al, 2006). our findings are distinct in that this is the first study to apply an emerging data analytic approach well suited for substance use outcome data to the study of parent and peer influences on collegiate alcohol use.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…our findings provide tangible evidence that this important context remains a salient one for alcohol use into the college years. second, although we did not directly investigate the importance of risk and protective factors, our findings can also be interpreted within this framework (hawkins et al, 1992;Jessor et al, 1995;Jessor et al, 2006). our findings are distinct in that this is the first study to apply an emerging data analytic approach well suited for substance use outcome data to the study of parent and peer influences on collegiate alcohol use.…”
Section: Discussionmentioning
confidence: 82%
“…abar and turrisi (2008) found that parental monitoring assessed at prematriculation predicted first semester alcohol use, with indirect effects on second semester drinking mediated by close friends' drinking. parental disapproval of drinking has also been negatively associated with college student alcohol use and consequences both cross-sectionally and longitudinally (boyle and boekeloo, 2006;Jessor et al, 2006). however, there has been mixed support for parents' discouragement or disapproval of drinking in predicting drinking status among nondrinking college students (lo and globetti, 1993;Weitzman et al, 2003).…”
mentioning
confidence: 99%
“…This trend has also been documented internationally, in countries such as Italy (DiGrande, Perrier, Lauro, & Contu, 2000), Spain (Caamaño-Isorna, Corral, Parada, & Cadaveira, 2008), the United Kingdom (Davoren, Demant, Shiely, & Perry, 2016), France (Tavolacci et al, 2016), Sweden (Vaez & Laflamme, 2003), New Zealand (Kypri et al, 2009), and, most extensively, in the United States (e.g. Fenzel, 2005;Jessor, Costa, Krueger, & Turbin, 2006).…”
mentioning
confidence: 70%
“…Binge drinking has been defined in the literature as consuming five drinks or more in one sitting or outing (e.g., Gliksman et al, 2003;Jessor et al, 2006;Pascarella et al, 2007;Schaffer, Jeglic, & Stanley, 2008). However, other researchers have elaborated upon this definition, and have further operationalized and supported the need to consider binge drinking as a gendered concept (e.g., Balodis et al, 2009;D'Alessio, Baiocco, & Laghi, 2006;Delucchi, Matzger, & Weisner, 2008;Simons, Christopher, & Mclaury, 2004;Wechsler, Dowdall, Davenport, & Rimm, 1995).…”
Section: Binge Drinking Operationalizedmentioning
confidence: 99%
See 1 more Smart Citation